Parameter Diskresi Birokratik: Studi Kasus Pemerintah Kota Surabaya dan Kabupaten Situbondo - Sri Juni Woro Astuti (Magister Ilmu Administrasi Publik, 2009)
This study sought to analyze the exercise of bureaucratic discretionary space in the areas of employee affairs in Surabaya Municipality and Situbondo Regency with regards to types of policy underlying the fulfillment of bureaucratic task, consideration underlying the decisions made at those bureaucratic levels, and acceptability of their outcomes. Conformity of discretion types with the types of public policy would promote attainment of policy goals in order for those policies to run effectively. However, capability of bureaucratic official officials in exercising their discretion in accordance with legal, ethical, professional, knowledge, and public interest parameters normatively acceptable was considered low. The available discretionary space was to a considerable extent exercised for